The Role of Islamic Boarding School Culture in Forming Discipline and Collective Cooperation in Darul Hijrah Islamic Boarding School - Salabi, Ahmad (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The culture of Islamic boarding schools has increasingly been recognized as a crucial medium for character education, especially in fostering discipline and cooperation among students amid globalization, which often challenges moral values and social solidarity. This study aims to examine the role of pesantren culture in shaping discipline and collaboration between male and female students at Darul Hijrah Islamic Boarding School. Using a descriptive qualitative method, the research employed in-depth observation, interviews with ustadz and ustadzah, and document analysis to capture formal and informal practices of daily life, religious routines, and collaborative activities. The findings reveal that strict rules, habitual congregational prayers, structured learning, and cooperative tasks significantly contribute to the development of discipline and social solidarity among students. Role modeling by teachers and a supportive pesantren environment were identified as key factors, while challenges arose from differences in individual motivation, student backgrounds, and external influences. Students perceive discipline not merely as an obligation but as a life value extending beyond the pesantren. In contrast, cooperation is internalized as practical experience in solidarity, equipping them for future social life. This study contributes a new perspective by demonstrating that internalizing pesantren culture involves reflective meaning-making rather than mere normative compliance. The research also implies that educational institutions, both boarding schools and formal schools, can strengthen student character by integrating structured routines, religious practices, and collaborative activities to foster long-term discipline and cooperative behavior.